The Influence of Service Quality, Perceived Value, Customer Satisfaction and Brand Trust towards Customer Loyalty in Subscription Video on Demand - Prabjit, Prabjit; Salim, Cynthia Viorenza; Kusumawardhani, Annisya; Gunadi, Willy (Budapest International Research and Critics Institute-Journal (BIRCI-Journal), 2021)
Due to the pandemic, the subscription of video on demand is increasing. This study provides a framework for customer loyalty of Subscription Video On Demand (SVOD). This study aims to determine how service quality, perceived value, customer loyalty, satisfaction, and brand trust affect SVOD. Data we recollected by using questionnaires through online forms from 200 subscribers of video on demand from Greater Jakarta who had used their expenses to pay the SVOD. Explanatory research method is applied in this research. The data were analyzed using structural equation modeling and using SmartPLS to analyze the data. According to the data analysis results, satisfaction positively impacted service quality, brand trust, and perceived value. Moreover, loyalty in SVOD influence negatively, whereas brand trust gives a substantially positive influence on loyalty in SVOD.